Development and Characterization of Film-Forming Solution Loaded with Syzygium cumini (L.) Skeels for Topical Application in Post-Surgical Therapies - Rosinéia Aparecida Vilela Cebrian; Mariana Dalmagro; Mariana Moraes Pinc; Guilherme Donadel; Larissa Aparecida Engel; Reinaldo Aparecido Bariccatti; Rafael Menck de Almeida; Kelen Menezes Flores Rossi de Aguiar; Emerson Luiz Botelho Lourenço; Jaqueline Hoscheid (MDPI AG, 2024)
Background/Objectives: Considering the antioxidant and antimicrobial properties attributed to compounds in Syzygium cumini extract, this research aimed to advance postoperative therapeutic innovations. Specifically, the study assessed the physicochemical properties of a film-forming solution (FFS) incorporated with S. cumini, evaluating its therapeutic potential for postoperative applications. Methods: The S. cumini extract was meticulously characterized to determine its chemical composition, with particular emphasis on the concentration of phenolic compounds. Antioxidant and antimicrobial assays were conducted to assess the extract's efficacy in these domains. Following this, an FFS containing S. cumini was formulated and evaluated comprehensively for skin adhesion, mechanical and barrier properties, and thermal behavior. Results: The antioxidant and antimicrobial activities of the S. cumini extract demonstrated promising results, indicating its potential utility as an adjunct in postoperative care. The developed FFS exhibited favorable physicochemical properties for topical application, including adequate skin adhesion and appropriate pH levels. Moreover, chemical and thermal analyses confirmed the formulation's stability and the retention of the extract's beneficial properties. Conclusions: Overall, the findings suggest that the S. cumini-loaded FFS holds significant potential as a valuable therapeutic tool for post-surgical management.